White bones in the soil : modes of narrativising in Kazuo Ishiguro's the buried giant - Png, Denise Wei Ting (2016)
Using Hans Blumenberg's theory of myth, this paper looks at the ways in which different characters in Kazuo Ishiguro's "The Buried Giant" construct their identity narratives.